Cultivation Practices of Sugarcane: An Analysis of the Competitiveness of Sugarcane Suppliers in Brazil - de Amorim, Fernando Rodrigues [UNESP]; Queiroz, Timóteo Ramos [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Lourenzani, Wagner Luiz [UNESP] (Springer Nature, 2021)
To ensure the competitiveness of sugarcane production chains, it is necessary to invest in new technologies and management practices at all stages of production, especially in cultivation practices. The question arises as to which production system presents the best competitiveness index (CI) for the sugarcane crop in Brazil. Thus, scientific studies are required for management and provide inputs for the maximization of productivity; total recoverable sugar; sugarcane cutting medium; and the minimization of average total costs cultivation practices of sugarcane. The aim of this study is to analyze the cultivation practices of sugarcane through competitiveness indexes. In this study, 55 suppliers from the Central-South region in Brazil provided data for the 2019/2020 season. The questionnaire was validated through an initial application and approved in the first round using the Delphi technique. A CI was raised to determine the best production system and for descriptive analysis and to evaluate the Spearman’s correlation profile of systems used by suppliers. The results revealed that in cultivation practice, the use of variable rate decreased the cost of production, whereas fixed rate increased profit maximization. The suppliers produced 88 tons/ha, which was greater than the average production in Brazil.
Keywords: Competitiveness index; Cost optimization; Fixed rate; Profit maximization; Variable rate